Heavy Metal Biosorption Characteristics of the Submerged Aquatic Plant (Nasturtium officinale) - OKUMUS*, V.; BASARAN†, D.; ONAY†, A. (Asian Journal of Chemistry, 2009)
In the present investigation an aquatic plant, Nasturtium officinale was examined for its biosorption ability of heavy metal ions. The results obtained from biosorption experiments were used to understand the driving forces that govern the interaction between metal ions and biosorbent. The experimental biosorption data were fitted to the Scatchard plot, Langmiur and Freundlich isotherms. According to the parameters of the Langmiur isotherm, the maximum biosorption capacities of Cd2+ and Co2+ were 0.56 and 0.49 mg/g, respectively. In view of Freundlich isotherms, the maximum biosorption capacities of Cd2+ and Co2+ were 2.23 mg/g for both of metal ions.